IMPLEMENTASI GAME BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI SISWA SEKOLAH DASAR - Sanki, Herlaksono Aditya; Listyarini, Ikha; Kholifah, Putri Nor; Purnamasari, Iin (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Basic skills that must be possessed by elementary school students are literacy and numeracy skills. Skills and numeracy are important for an individual's capacity to apply thinking. Thinking is the capacity to examine and understand statements, through practice by controlling language and numerical signs experienced in everyday life to show approval orally or in writing, so that skills and numeracy become the main units for dealing with everyday problems and answering the challenges of the 21st century. This test is expected to train the educational and numeracy skills of elementary school students through the application of Game Based Learning. The technique used in this study is PTK or Homeroom Movement Investigation with the Stephen Kemmis and Mc. Taggart test plan model consisting of two stages of preparation. Based on these figures, the results of Game Based Mastering show PTK of 53% and Exploration of Learning Activities of 89%. While the skills show results of 51% and 68%. The completion of this study shows how the implementation of game-based learning can improve the academic and numeracy skills of students at SD Pedurungan Tengah 02.